New Straits Times, 15 January 2007 - Anis Ibrahim (The New Straits Times Press (M) Bhd, 2010)
On Dec 18,newly installed Kuala Lumpur mayor Datuk Ab Hakim Borhan proposed a levy on vehicles entering the city centre during peak hours. Ab Halim said the levy, intended to reduce traffic congestion, was justified as commuters could rely on the city's improved public traspotation.